Meteorological Observation in the Central Kathmandu Valley using the First Automated Meteorological Observatory of Tri-Chandra Multiple Campus - Acharya, Ram Hari; Adhikary, Sunil; Mahato, Shiv Kumar; Gautam, Narayan Prasad (Jalawaayu, 2022)
The main meteorological features of the central Kathmandu valley, Nepal were investigated by means of the dataset recorded by the automated meteorological observatory of Tri-Chandra Multiple Campus (1295m a.s.l. and 27.708217oN, and 85.315369oE) from May 2018 to April 2021. Initially, this observatory was installed for laboratory work with promoting clean energy resources by phasing out mercury instruments, since the onset of the coronavirus pandemic the growing importance of having resilience in the meteorological observation system has been more clearly demonstrated. Now, this automated real-time meteorological observatory becomes a backbone of our academic system, whereby students and teachers can have direct access to the data source and can self-analyze the prevailing atmospheric condition. As the detailed picture of the seasonal and diurnal cycle of meteorological parameters over the central Kathmandu valley, Ranipokhari premises, has been unavailable, this study tries to outline the prevailing surface air condition more precisely. The analysis was made on the basis of seasonal and diurnal variations of the weekly and monthly mean of meteorological parameters. The results confirmed that the surface heating by solar radiation mainly drives the variation in surface meteorological parameters. It was observed that the daily minimum temperature is recorded just before dawn and a maximum by mid-day with lagging to the daily solar maxima. In the time, the relative humidity was derived in a reverse cyclic pattern. During the summer monsoon and winter monsoon season, when the diurnal range of solar intensity became lower, also the temperature, relative humidity, and wind strength possessed a smaller diurnal range. The seasonal rainfall distribution in central Kathmandu valley also agreed with the climatic normal, about 80% of the total annual rainfall is solely contributed by the summer monsoon season. Summer monsoon possesses some incoherent phase pattern of the diurnal cycle of mean rainfall with two comparable peaks, one as mid-night/nocturnal maxima and the other as of late afternoon maxima. While, the early morning rainfall intensity tends to decrease and attains its minima around late morning, whereby, the frequency of drizzle type of rainfall was most dominant.